Connection Knowledge to Attitude Mother Pregnant About Utilization Book of "KIA" - Sari , Yenny Okvita; Wulandatika , Darmayanti (Jurnal EduHealth, 2023)
Utilization of maternal and child health services is currently still hampered by a lack of mothers' knowledge and attitudes regarding dangerous signs of pregnancy and other related matters of pregnancy, and it is essential to give understanding to pregnant women regarding the book Maternal and Child Health (KIA). The average mother knows That the KIA book is only used during pregnancy. This research uses methods of interviews to determine the relationship between the knowledge and attitudes of pregnant women regarding the use of KIA books at Banjarmasin health centers. This type of research is analytical descriptively using the chi-square test. The results showed that knowledge of pregnant women's attitudes regarding the use of KIA books obtained a p-value of 0.009 with a degree of 95% confidence (p<0.05), so the obtained conclusion is connection significant between knowledge of the attitudes of pregnant women regarding the use of KIA books, as well as necessity counseling periodically because not all women are pregnant remember or know Benefits of the KIA book.